GRANOS DE POLEN DE LA FORMACION LAS CABRAS (TRIASICO), EN SU LOCALIDAD TIPO, PROVINCIA DE MENDOZA, ARGENTINA. PARTE 1 (Ameghiniana, 2013)
The first systematic study of monosaccate and bisaccate pollen grains of the type locality of Las Cabras Formation (Triassic), Potrerillos area, Mendoza, is presented. Thirty six species of pollen grains are described, belonging to the foIlowing genera: Vesicaspora, Accintisporites, Daughertyspora, Callialasporites, Potonieisporites, Alisporites, Falcisporites, Vitreisporites, Klausipollenites, Podosporites, Pityosporites, Brachysaccus, Podocarpidites, Sulcatisporites, Protodiploxypinus, Chordasporites, Platysaccus, Parillinites, Illinites and Angustisulcites. Fifteen genera are reported for the first time in Argentina. The botanical affinity, chronological range and regional and global distribution of alI species included in this study are given. The age of Las Cabras Formation microflora, in its type locality, is Middle Triassic (late Anisian-Landinian).